Insecticidal potential of Areca catechu nut extract against multiple life stages of Aedes aegypti and Aedes albopictus - Zainab Rahman; Madhuri Bharathithasan; Lau Yee Ling; Olawale Quazim Junaid; Intan H. Ishak; Rajiv Ravi (PLoS ONE, 2026)
This study investigates the insecticidal efficacy of Areca catechu nut extract against Aedes aegypti and Aedes albopictus , in response to increasing insecticide resistance, declining effectiveness of conventional agents, and environmental safety concerns. The primary objectives were to evaluate the adulticidal, ovicidal, and oviposition deterrent activities of methanolic A. catechu nut extract across a concentration range of 300–2000 ppm, and to identify its major bioactive constituents. Laboratory bioassays were conducted following World Health Organization protocols. The extract induced dose-dependent adult mortality, with LC 50 values of 767.501 ppm for Ae. aegypti and 758.278 ppm for Ae. albopictus . Ovicidal assays showed progressive increases in egg mortality, reaching 100% at 1600 ppm for Ae. aegypti and 1400 ppm for Ae. albopictus . In oviposition deterrent tests, complete inhibition of egg-laying occurred at concentrations of 900 ppm and above under both dual-choice and non-choice conditions. Observational data confirmed strong repellence, as gravid females avoided treated substrates even in the absence of alternatives. Liquid chromatography–mass spectrometry analysis identified arecoline, arecaidine, and N-lauryldiethanolamine as key constituents with known inhibitory effects on neural and detoxification enzymes in insects. This research provides a comprehensive assessment of A. catechu nut extract across multiple mosquito life stages and behavioural endpoints, demonstrating its broad-spectrum efficacy. The results support its potential as a sustainable, plant-derived bioinsecticide for integrated vector control programs targeting Aedes mosquitoes and associated disease transmission.